Construction of Rice Milling Unit (RMU) as an Effort to Provide Price Certainty for Farmers and Meet the Rice Needs of the Community - Arnawa, I Ketut; Budiasa, I Made; Made Suryana (Faculty of Agriculture Udayana University, 2025)
BACKGROUND AND OBJECTIVES Farmers in Badung Regency face uncertainty in rice prices, which affects their welfare. Price instability makes it difficult for farmers to earn a decent and sustainable income. To overcome this problem, constructing a Rice Milling Unit (RMU) is one strategic solution, as it can guarantee the price of rice received by farmers. This study aims to analyze the feasibility of RMU development from three main aspects: rice availability, community rice demand, and financial feasibility. METHODS This descriptive study was conducted in Badung Regency, Bali Province. Data collection was carried out through questionnaires and interviews with farmers, business actors, and relevant policymakers. The feasibility analysis of rice availability and rice demand was conducted descriptively. Meanwhile, financial feasibility was analyzed using several investment criteria, namely Net Present Value (NPV), Net Benefit Cost Ratio (Net B/C), Internal Rate of Return (IRR), and Payback Period. FINDINGS The study's results indicate that the construction of an RMU is feasible in Badung Regency. This region has production and consumption potential that supports the project in terms of rice availability and demand. From the financial aspect, the project shows profitable results with an NPV of Rp. 171,931,999.193, Net B/C of 1.2900, IRR of 25.05%, and a Payback Period of 1.44 years. CONCLUSION The construction of a rice milling unit in Badung Regency is an appropriate solution to address the uncertainty farmers face in paddy prices. In addition to ensuring stable paddy prices, this development supports rice availability for the community at stable prices